2023
DOI: 10.1037/fam0001048
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of parents’ schemas of their children: Unique relations to sensitivity and learning support among families living in poverty.

Abstract: This study examined how distinct aspects of parents’ schemas of their children are related to caregiving behaviors. It included 242 families with toddlers and young children, most of whom were living in poverty (37% White, 25% Black, 19% Latine, 17% Multiracial, and 2% Asian; child age = 21–39 months; median family income = $1,555 per month). The elaboration and emotional valence of parents’ schemas were coded from brief responses to open-ended questions about children’s personality; observations of parents’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…The study sheds light on the complex interplay between poverty and childcare, demonstrating that poverty in rural areas can lead to a variety of unique challenges with far-reaching consequences for children's development. Furthermore, it has been found that caregivers with lower levels of education and with scarce economic resources have less favorable attitudes towards childcare (Stahl et al, 2018;Ma et al, 2023), and are less sensitive when correctly interpreting the signals from the child and respond effectively to them (Engbretson et al, 2023). Likewise, other sociodemographic data that influence parental attitudes are the mother´s age, the number of children, and the differences between urban and rural areas (Mesman et al, 2016;Heidari et al, 2018;Bornstein et al, 2020;Paramashanti et al, 2022;Fang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The study sheds light on the complex interplay between poverty and childcare, demonstrating that poverty in rural areas can lead to a variety of unique challenges with far-reaching consequences for children's development. Furthermore, it has been found that caregivers with lower levels of education and with scarce economic resources have less favorable attitudes towards childcare (Stahl et al, 2018;Ma et al, 2023), and are less sensitive when correctly interpreting the signals from the child and respond effectively to them (Engbretson et al, 2023). Likewise, other sociodemographic data that influence parental attitudes are the mother´s age, the number of children, and the differences between urban and rural areas (Mesman et al, 2016;Heidari et al, 2018;Bornstein et al, 2020;Paramashanti et al, 2022;Fang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%